Maternal high-fat diet during pregnancy or lactation changes the somatic and neurological development of the offspring - Cristiano Mendes-da-Silva; Catherine Ássuka Giriko; Laís Vales Mennitti; Lilian Fazion Hosoume; Tayane dos Santos Souto; Alexandre Valotta da Silva (Arquivos de Neuro-Psiquiatria)
The maternal exposure to high fat diet (HFD) during pregnancy and breastfeeding have been considered an important inducer of alterations in offspring normal programming, both in animals and humans, and may disturb brain development. In the present study we investigated the somatic and sensory-motor development of the offspring from rat dams fed a HFD, compared with dams fed a control diet, during pregnancy or lactation. Indicators of the body growth, physical maturation, and reflex ontogeny were evaluated. Offspring of dams fed a HFD showed reduced weight and body growth, delayed physical maturation, and delayed maturation of the physiological reflexes, such as vibrissa placing, auditory startle response, and free-fall righting. Our findings suggest that maternal HFD during pregnancy or lactation modifies somatic and neurological development of the offspring, possibly increasing the risk of neuroendocrine and neuropsychiatric disorders later in life.